PENGARUH KONSENTRASI HCl DALAM PROSES HIDROLISIS PADA PEMBUATAN BIOETANOL KULIT PISANG KEPOK - Alfiansyah, Irsyad; Mujiarto, Sigit; Sulistiyo, Raka Mahendra; Dewi, Rany Puspita (POLITALA PRESS, 2025)
Dependence on fossil fuels results in depletion of petroleum. In solving this problem, it is necessary to use alternative fuels in the form of bioethanol. Bioethanol is made by utilizing kepok banana peels. There are quite a lot of banana peels, approximately one third of the bananas that have not been peeled. This study was conducted to analyze the ethanol content, water content, density, and viscosity of kepok banana peel bioethanol. This study uses an experimental method of the effect of HCl concentration (2%, 5%, and 8%) in the hydrolysis process in the manufacture of kepok banana peel bioethanol. From the results of the study, the best bioethanol characteristics at a concentration of 2% HCl with an ethanol content of 9%, a water content of 70.52%, a density of 0.9861 g/ml, and a viscosity of 0.010768212 dPa.s. The characteristics of the bioethanol produced are different from the characteristics of pertalite.